2010
DOI: 10.1021/es1025195
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate, Nitrate, and Iodide Intake through Tap Water

Abstract: Perchlorate is ubiquitous in the environment, leading to human exposure and potential impact on thyroid function. Nitrate can also competitively inhibit iodide uptake at the sodium-iodide symporter and thus reduce thyroid hormone production. This study investigates the intake of perchlorate, nitrate, and iodide attributable to direct and indirect tap water consumption. The National Health and Nutrition Examination Survey collected tap water samples and consumption data from 3262 U.S. residents during the years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 41 publications
0
50
2
Order By: Relevance
“…Recent studies have found perchlorate in finished water, with median levels up to 1.2 μg/L [95]. Using individual tap water consumption data and body weight, the median perchlorate dose attributable to tap water was 9.1 ng/kg-day.…”
Section: Perchloratementioning
confidence: 95%
“…Recent studies have found perchlorate in finished water, with median levels up to 1.2 μg/L [95]. Using individual tap water consumption data and body weight, the median perchlorate dose attributable to tap water was 9.1 ng/kg-day.…”
Section: Perchloratementioning
confidence: 95%
“…One of the main health hazards is connected with the very fact that perchlorate interferes with iodide uptake in the thyroid gland [35,36]. In large doses, it has been linked to anemia and fetal brain damage [30,35].…”
Section: Clomentioning
confidence: 99%
“…[36][37][38] Regarding thyroid function, nitrate can competitively inhibit iodide uptake, 39,40) which may cause a reduction in thyroid hormone production. 41) In an assessment of the Iowa Women's Health Study, high nitrate intake through drinking water consumption and private well use seemed to increase the risk of ovarian cancer in postmenopausal women. 38) Similarly, a study by Ward et al 26) found a significantly increased risk of both thyroid cancer and hypothyroidism in females with high dietary nitrate intake living in the same region, but no significant association was found for nitrate ingestion via drinking water.…”
Section: Discussionmentioning
confidence: 99%